Research progress on self-management strategies in patients with low anterior resection syndrome (低位前切除综合征患者自我管理策略研究进展) - YI Ranran (易冉冉); WEN Ruizhen (温瑞珍); WANG Miaolan (王淼兰); ZHENG Xiaoxuan (郑筱暄); PENG Hui (彭慧) (中西医结合护理)
Anal preservation surgery is the mainstream treatment for rectal cancer, and low anterior resection syndrome is a common complication after anal preservation surgery. Low anterior resection syndrome has a long course of disease, which has a serious impact on the quality of life of patients, and there is no effective treatment measure. This paper summarized the pathophysiological mechanism, evaluation and treatment of low anterior resection syndrome, expounded the research progress in self-management strategies in recent years, and described them in detail from the aspects of diet adjustment, lifestyle and psychological adjustment, so as to provide theoretical basis for medical staff to implement intervention measures and improve the quality of life of patients with low anterior resection syndrome after rectal cancer surgery. (保肛手术是目前直肠癌的主流治疗方式, 低位前切除综合征(LARS)是保肛术后常见的并发症。LARS病程长, 难治愈, 严重影响患者的生活质量。本文系统梳理了LARS的病理生理机制、评估方法及治疗策略, 重点总结了近年来在自我管理领域的研究进展, 从饮食调整、生活方式干预及心理调适等方面进行了详细阐述, 旨在为医护人员制定干预措施和改善LARS患者生活质量提供理论依据。)